Análise comparativa entre amostragem de solo convencional e amostragem de solo para agricultura de precisão - Pötter, Marcel Borges (2014)
Soil analysis is one of main resources for obtaining agriculture with quality and gains, being even the first way in planning this activity, to determine the necessity and quantity of fertilizer that each land needs, according recommendation of fertilization and setting. Therefore, this research is the main objective to evaluate the difference between soil analysis in conventional agriculture and soil analysis in precision agriculture. The research was developed in Restinga Seca, RS, at two distinct properties, was developed the system of conventional agriculture and, the precision agriculture. In conventional agriculture, soil analysis was put into action by this way: from an area of 20 hectares were collected from 15 dots, with a spade, mere samples that are put in a bucket, where formed a composed sample, to be send to laboratory. In precision agriculture the soil analysis was collected by geo-referencing method using GPS, establishing exact dots through the Coordinates X and Y , and in this way forming the sample grate. It was collected one sample each two hectares, more nine samples in V around each geo-referent dot, for send to laboratory. Soil levies were done by a four-cycle. The advantages of precision agriculture with regard to conventional agriculture are economic reduction of fertilizer, productivity increasing, land sustentation, because the correct manure use and economy of agricultural agro-toxins. The disadvantage is the high cost of the equipments to develop the precision agriculture. After all, the benefits and the increasing of the new method use corroborate evidence to prove its superiority in relation to conventional agriculture.